T cell-derived lymphotoxin limits Th1 response during HSV-1 infection. Issue 1 (December 2018) - Yang, Kaiting; Liang, Yong; Sun, Zhichen; Liu, Longchao; Liao, Jing; Xu, Hairong; Zhu, Mingzhao; Fu, Yang-Xin; Peng, Hua
Abstract Though lymphotoxin (LT) is highly expressed by type I helper T (Th1) cells, its contribution to CD4+ T cell differentiation during infections and diseases remains a mystery. In HSV-1 infection, we observed that LTβR signaling is required to limit the Th1 response. Using bone marrow chimeric mice, mixed-T-cell chimeric mice, and LTβRin vivo blockades, we unexpectedly observed that LT, especially T cell-derived LT, played an indispensable role in limiting the Th1 response. The LTβR-Ig blockade promoted the Th1 response by increasing infiltration of monocytes and monocyte-derived DCs and up-regulating IL-12 secretion in the lymphoid environment. Our findings identified a novel role for T cell-derived LT in manipulating Th1 differentiation.